1984
DOI: 10.2337/diab.33.9.838
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Improvement in Glucose Metabolism After Chronic Glyburide Therapy

Abstract: The effect of glyburide on glucose metabolism was examined in 10 non-insulin-dependent diabetic subjects (NIDDM) and 7 young, control subjects. After 3 mo of glyburide treatment in NIDDM, fasting plasma glucose declined from 198 to 141 mg/dl (P less than 0.01) without change in fasting insulin levels. Basal hepatic glucose production (HGP) was slightly elevated in NIDDM versus controls (2.35 versus 2.18 mg/kg X min, P = NS) and was positively correlated with the fasting glucose concentration (r = 0.93, P less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(64 citation statements)
references
References 17 publications
6
57
1
Order By: Relevance
“…In addition, glucose metabolites and incretins (e.g., glucagon-like-peptide-1, GLP1) can affect secretion at various stages downstream of K ATP [14,28,38,54]. Nevertheless, the ability of highly selective K ATP drugs (KCOs and inhibitory SU drugs) to modulate GSIS both in vivo and in vitro underscores the central role of K ATPdependent regulation [117,130].…”
Section: Role Of K Atp In Insulin Secretion From the Pancreatic β-Cellmentioning
confidence: 95%
“…In addition, glucose metabolites and incretins (e.g., glucagon-like-peptide-1, GLP1) can affect secretion at various stages downstream of K ATP [14,28,38,54]. Nevertheless, the ability of highly selective K ATP drugs (KCOs and inhibitory SU drugs) to modulate GSIS both in vivo and in vitro underscores the central role of K ATPdependent regulation [117,130].…”
Section: Role Of K Atp In Insulin Secretion From the Pancreatic β-Cellmentioning
confidence: 95%
“…4 (see also Table 2). The calculated R d is now greater than R a , so that R a -R d is negative, providing the drive which decreases C [for example see the first of the equations (14)]. There is a definite decrease in the calculated R a , which however, continues to appear high, particularly in the first several hours of the study in diabetic subjects (Fig.…”
Section: Taking the Non-steady-state Into Account: The One-compartmenmentioning
confidence: 97%
“…Impaired hepatic uptake would also increase net splanchnic production [1,9,11,13]. Nevertheless, other investigators [14,15,16,17,18,19] concluded that glucose production is altered only marginally during fasting hyperglycaemia and changes substantively only when there is a high increase of glucose concentrations. The discussion centred largely on the methodology.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They generally lower circulating glucose levels by approximately 20% and work best in patients of normal or slightly increased body weight. It has also been shown that sulfonylureas can enhance peripheral tissue sensitivity to insulin [7][8][9]. Glyburide, a second-generation sulfonylurea, was initially demonstrated not to cross the placenta in signifi cant amounts and fetal concentrations reached no more than 1% to 2% of maternal concentrations [10][11][12].…”
Section: Glyburidementioning
confidence: 99%